Process management as a factor in increasing the efficiency of an electric grid enterprise - O. V. Khalikova (Путеводитель предпринимателя)
The power industry is essentially a monopoly industry with a high degree of centralization ofdecision-making at the level of the executive apparatus, which implements a functional management approach. With the external integrity and monolithicity of the management system, it includes a number of contradictions that impede the effective development of the enterprise, which may be allowed by the implementation of the process approach to management. The article discusses the conditions for the effectiveness of the application of the process approach to the management of an electric grid company, the main of which is customer focus. The prerequisites for changing the relationship between the technical unit and the block for the sale of electric grid services are given. Barriers to the transition from functional to process control are also described. The author proposes to introduce elements of a process approach into the functional structure ofthe electric grid company, as well as delegation ofauthority to make operational management decisions to lower levels of management. The ways of transition from vertical management to increasing its productivity and the effectiveness ofthe company as a whole through the development of decentralization and horizontal ties are also indicated.